Barriers and motivations for participation in preventive vaccine clinical trials: Experience of 5 clinical research sites. Issue 44 (16th October 2019) - Detoc, M.; Launay, O.; Dualé, C.; Mutter, C.; Le Huec, J.-C.; Lenzi, N.; Lucht, F.; Gagneux-Brunon, A.; Botelho-Nevers, E.
Abstract: Recruitment in preventive vaccine trials (PVT) is challenging due to common barriers to clinical research and lack of vaccine confidence. Identifying determinants of participation can help to improve recruitment. A prospective survey was conducted in 5 French clinical investigational sites. People asked to participate in a PVT were given a questionnaire whether they decided to participate or not in the trial. A total of 341 people answered the survey: 210 accepting and 131 declining to participate in a PVT. Acceptors were significantly younger (38.5 vs 54.9 years old), more likely to be involved in early phase trials, had a higher level of education (p < 0.005) and a significantly better general opinion concerning vaccines (92.3% versus 72.3%, p < 0.005) compared with those who declined. Factors associated with acceptance or refusal were evaluated in 224 people in the 4 sites where both groups were included. In a multivariate analysis, three factors: older age, having heard about PVT through multiple sources and financial incentives were significantly associated with refusal to participate in the PVT. A generally favourable opinion of vaccines was associated with acceptance. The main motivation for participation was altruism (93.2%) whereas fear of side effects was at the forefront of the barriers (36.6%). Information given by the physician was a key point for decision-making in 70.2% of those who accepted. In brief, vaccine hesitancy may decrease recruitment in PVTs; reinforcing altruism and quality of information given are key points in acceptance of participation in PVT.